2020
DOI: 10.1590/1516-4446-2020-0804
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal treatment for a Brazilian case of hikikomori

Abstract: the twins continued to live with their father, and psychotherapy was recommended to all evaluees. These cases demonstrate that the assessment of parental alienation demands attentive study of the legal process, multiple evaluations carried out with different family members, and collateral sources of information. In a context of conjugal disputes and possible psychiatric disorders (in parents or children), it is mandatory to characterize the child behavior as consistent in rejecting one parent due to manipulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…In contrast, some reported feeling freed from restraints and timelines and enjoying their seclusion [ 53 ]. Poor hygiene behaviors were reported in a minority of hikikomori [ 38 , 49 , 72 ], with one person defecating and urinating in jars or bottles in his room [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, some reported feeling freed from restraints and timelines and enjoying their seclusion [ 53 ]. Poor hygiene behaviors were reported in a minority of hikikomori [ 38 , 49 , 72 ], with one person defecating and urinating in jars or bottles in his room [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“… Matsuguma et al [ 77 ] ? X Silić et al (2019) X Roza et al [ 72 ] X X JBI for Qualitative Study Is there congruity between the stated philosophical perspective and the research methodology? Is there congruity between the research methodology and the research question or objectives?…”
Section: Methodsmentioning
confidence: 99%
“…4,6 Family interventions, comorbidity treatment, online interventions, physical activity, multiple psychotherapeutic approaches, social skills training, etc., have been indicated as potentially useful strategies for hikikomori cases. 3,[7][8][9][10][11] Nevertheless, the evidence to support these treatment approaches is weak, mainly due to a lack of studies on the topic. 3,6 In 2020, updated diagnostic criteria 4 were proposed for hikikomori, with the inclusion of a severity classification based on the weekly frequency the individual leaves his home or room.…”
mentioning
confidence: 99%
“…4,10 The prevalence of hikikomori in Brazil is unknown due to a lack of empirical research on the phenomenon; however, the syndrome has been reported three times in Brazilian patients. 9,12,13 Recently, our group described the complete treatment program for one of these cases. The patient reported substantial clinical improvement after a multimodal intervention strategy, including pharmacological treatment of comorbidities, family psychoeducation, and the use of different psychotherapy techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation